Activity Engagement in Residential Care Settings: Findings from the National Survey of Residential Care Facilities. Issue 2 (3rd April 2019) - Sengupta, Manisha; Zimmerman, Sheryl; Harris-Kojetin, Lauren
Abstract: Assisted living and similar residential care is an important source of care for elders, including those with dementia. Meaningful activities may help residents maintain function, improve self-esteem, and enhance quality of life. Using data from the 2010 National Survey of Residential Care Facilities, this study identifies the extent of resident engagement in different types of activities; examines the extent to which cognitive status, other resident characteristics, and residential care community characteristics relate to activity engagement; and, among cognitively impaired residents, assesses whether being in dementia-specific settings is associated with activity engagement. Compared with persons without cognitive impairment, those with severe cognitive impairment are less likely to go on outings (79% versus 36%) and talk with family and friends (85% versus 72%). Residents with mild to severe cognitive impairment have higher participation in leisure activities than other residents if they live in dementia-specific settings (73% higher) than those who do not.